The pumpkin monster - Gates, Susan (Cambridge : Cambridge university press, 2016)
Hanna's pumpkin grew into a monster. Can Hanna save the people? Blue Band books feature more complex stories with several characters and episodes within one story to support comprehension development. Greater variation in sentence patterns helps readers to self-correct independently. Contains full teaching support including learning outcomes, curriculum links and follow-up activities.
Keywords: English; Cambridge - English